الواقع والآثار في العلاقات التجارية بين تلمسان والسودان الغربي خلال العهد الزياني 633-962ه/1235-1554م - قريان, عبد الجليل (Université de M'sila, 2017)
الملخص: تمكنت تلمسان في العصر الوسيط الزياني من نسج علاقات تجارية مميزة مع السودان الغربي، مستفيدة من الموقع الجغرافي للمدينة التي كانت مركز التقاء لثلاثة اتجاهات أساسية في حركة التجارة الاقليمية شرقا وشمالا وجنوبا، ومستغلة الفراغ السياسي الذي تركته دولة الموحدين في توسيع حدودها السياسية والتجارية نحو سجلماسة، مدعمة في كل ذلك بتنوع إنتاجها المحلي والعابر في الوقوف بثبات في ترسيم الخارطة التجارية نحو السودان الغربي وأوروبا. وكان للشركات التجارية التلمسانية دور فعال في التموقع في المراكز التجارية والربط بينها بواسطة وكلاء تجاريين ساهموا في تنشيط الحركة التجارية والتمكين لها وترسيخها في إطار التفاعل بينهم وبين الطبقة السياسية في كل من تلمسان والسودان الغربي مما كان له أثره المحمود في استمرارها لعقود، مستهدفة في ذلك مختلف السلع الأساسية التي كانت تتدفق بينها بأريحية. ولم تقتصر آثار الحركة التجارية نحو السودان الغربي على الجانب الاقتصادي فحسب بل تجاوزت ذلك إلى التأسيس لشبكة من العلاقات السياسية والثقافية والحضارية بين ضفتي الصحراء حيث كانت بين الدولة الزيانية والسودان الغربي وفادات ومراسلات، كما ساهم علماؤها(تلمسان) وغيرهم في نشر الإسلام والثقافة الإسلامية، وكانت لذلك آثارها الطيبة على المستوى السياسي والشعبي إذ أصبحت تعج بالعلماء والفقهاء والقضاة، وبَقِيَتْ على ذلك إلى عصرنا. الكلمات المفتاحية: القوافل التجارية - السودان الغربي- النشاط الاقتصادي- المراكز التجارية- الابعاد السياسية والحضارية. Summary: Tlemcen has established special relationships with southern Sudan in the medieval era. Taking benefit from the geographical location of the city that was the central node of three basic directions in the territorial commercial movement from east, north and south, and taking advantage from the political vacuum left by the state of muwahidin by enlarging its political and commercial frontiers towards Seldjelmassa, supported by the diversity of its local and transitory production, to stand firm for drawing the commercial map towards southern Sudan and Europe. The Tlemceni commercial companies had a significant role, by their position in the commercial centers, relying between them through commercial agents who participated for the revitalization of the commercial movement, its establishment and its empowerment, through interaction between them and the political class in both Tlemcen and southern Sudan, the strong effect that allowed them to last for decades, targeting the diversity of essential goods that flowed in ease. The commercial movement impacts were not limited towards southern Sudan in the economical side only, but it surpassed it by establishing a network of political, cultural, and civilizational relationships between the two sides of the desert, there were communications and hospitality between Ziani state and southern Sudan, Tlemcen and its scholars had also contributed to spread Islam and Islamic culture, the fact that made its beneficial effects at the political and popular level, so that it has become crowded with Islamic scholars and judges, and stayed in this state until our age. Key words: commercial convoys - southern Sudan - economic activity - commercial centers -political and civilizational dimensions.
Keywords: القوافل التجارية ; السودان الغربي;النشاط الاقتصادي;المراكز التجارية;الابعاد السياسية والحضارية. commercial convoys ;southern Sudan ;economic activity ;commercial centers ;political and civilizational dimensions.